Stephen Stirk y Helen Sanderson (2013): Creating person-centred organisations. Strategies and tools for managing change in health, social care and the voluntary sector. Londres: Jessica Kingsley Publishers. - Cuervo Rodríguez, Tania (Revista Española de Discapacidad, 2016)
Reseña de la obra ’Creating person-centred organisations. Strategies and tools for managing change in health, social care and the voluntary sector’ (2013) de Stephen Stirk y Helen Sanderson.